Pengaruh level tapioka dan lama fermentasi terhadap kadar tanin dan mineral pada silase kulit pisang kepok - Theresia Nur Indah Koni; Tri Anggarini Yuniwaty Foenay (Jurnal Ilmu Ternak, 2020)
The aim of this research was to determine the effect of tapioca level and fermentation length on the content of calcium, phosphor, and tannin in silage from kepok banana peels. This research used ses factorial completely randomized design (4x3) consist of two factors, namely level of tapioca starch (5, 10, 15%) and fermentation length (7,14, 21 and 28 days) with three replication for each factors. The results of the research showed that tapioca level had significant effect (P<0,05) on the content of moisture, calcium, phosphor and tannin. Fermentation length had significant effect (P<0,05) on moisture and tannin  content, but had no effect on calcium and phosphor content. Interaction between treatments had significant effect (P<0,05) on moisture and tannin content. The best treatment combination in reducing tannin content was 10% tapioca inclusion and 21 days of fermentation length